A new semi-synthetic carboximidamide mitigates sickness behavior in mice - L. C. R. Hilgenberg; L. D. R. Acho; G. R. Batista; J. P. Moura-Neto; E. S. Lima; C. C. Veloso (Brazilian Journal of Biology)
Abstract In the course of an infection, increased pro-inflammatory cytokines cause diseased individuals to develop a set of adaptive behavioral changes, collectively termed as sickness behavior. The administration of the endotoxin LPS, the main component of the outer membrane of Gram-negative bacteria, leads to activation of the immune system, inducing inflammatory process in experimental models. A new carboxymidamide (DCHA), which has potential anti-inflammatory activity, may be a promising candidate in the development of a new drug for inflammatory diseases and control of sickness behavior. This study was conducted to evaluate the effects of a novel carboxymidamide on lipopolysaccharide-induced sickness behavior in mice. The animals were submitted to open field tests and forced swimming two hours after treatment with LPS (100 µg/kg). In addition, the mRNA expression of iNOS and pro-inflammatory cytokines (IL-1β, TNF-α and IL-6) from the blood, liver and kidney of these animals was also evaluated using quantitative real-time PCR. The administration of lipopolysaccharide (LPS, 100 µg/kg, i.p.) induced behavioral changes in the mice, such as decreased locomotor and exploratory activity in the open field test and an increase in the time the animal remained floating in the forced swimming, as well as increased mRNA expression of iNOS and the pro-inflammatory cytokines IL-1β, TNF-α and IL-6. Pretreatment with the new carboxymidamide attenuated the behavioral changes induced by LPS, and significantly reduced the expression of iNOS and pro-inflammatory cytokines in mice. Thus, our experimental results demonstrated that DCHA attenuated the sickness behavior induced by LPS. These results suggest that the observed pharmacological effect is due to the in vivo anti-inflammatory action via reduction of pro-inflammatory cytokines.